Elasmopus sivaprakasami sp. nov., a new species of amphipod (Senticaudata, Maeridae) from Gujarat State, India - Myers, Alan A.; Trivedi, Jigneshkumar N.; Gosavi, Swapnil; Vachhrajani, Kauresh D. (Zootaxa, 2018)
A new species of amphipod, Elasmopus sivaprakasami sp. nov., is described from India. It is found to be conspecific with material described from southern India nearly fifty years previously, but attributed at that time to a species described from Japan.